Growth and Yield of Acacia hybrid Trial Plots at Model Planted Forest in Sabal Forest Reserve - Elia, Ambrose (Universiti Malaysia Sarawak (UNIMAS), 2017)
Acacia hybrid is a hybridisation product between Acacia mangium and Acacia auriculiformis. Acacia hybrid inherited stem straightness from its female parent, A. mangium, and self-pruning and stem circularity from its male parent, A.auriculiformis. The study was conducted to assess the growth and yield of Acacia hybrid in trial plots. Diameter at breast height and total height of approximately 5.6 years old of Acacia hybrid trees in five plots with plot size of 25 m x 25m each were measured. Growth characteristic of Acacia hybrid was determined by evaluating the DBH, total height, basal area, volume and mean annual increment. The total height and merchantable height of all the trees in 5 plots was determined by using regression equation with the coefficient of determination R2 of 0.77 and 0.55, respectively. Regression equations were determined through relationship between DBH (independent variable) and the total and merchantable height (independent variable) following simple linear regression analysis. Mean of merchantable volumes over bark and under bark of the 5.6 years old of Acacia hybrid was 14.7 and 13.6 m3 /ha/year, respectively. The mean yield from the merchantable volume over bark was 82.7 m3 /ha. Survival rate of the 5.6 years old of Acacia hybrid was 84% with 931 stem density per hectare. This study had provided a better understanding about growth and yield of 5.6 years old Acacia hybrid in trial plots.